Flexible, ultralight, and high-energy density electrochemical capacitors using sustainable materials. (20th May 2022) - Pal, Bhupender; Matsoso, Joyce Boitumelo; Parameswaran, Abhilash Karuthedath; Roy, Pradip Kumar; Lukas, Dekanovsky; Luxa, Jan; Marvan, Petr; Azadmanjiri, Jalal; Hrdlicka, Zdenek; Jose, Rajan; Sofer, Zdenek
Highlights: Flexible, ultralight, current collector and binder-free energy storage device. Cost-effective device fabrication method. Excellent electrochemical performance and cycling stability. Abstract: Development of flexible, ultralight, scalable and non-leaking energy storage devices such as electrochemical capacitors that are on par with commercial standards and offer compliances while retaining safety remain a significant challenge for the realization of wearable devices. Generally, the bottleneck to the improvement of such devices is the need to use ecofriendly electrode and electrolyte materials with desirable surface, electrochemical and mechanical properties. Thus, this study provides a new platform for development of flexible, ultralight, freestanding electrochemical capacitor using a composite of cellulose/SWCNTs (CL/CNTs) electrode films and a new cellulose/NaHSO4 hydrogel electrolyte. Herein, we took advantage of the renewability and flexibility of cellulose in combination with the high conductivity and storage capacity of SWCNTs to create a high specific capacitance, energy and power density. Moreover, the new cellulose/NaHSO4 hydrogel electrolyte provided stable cycling, leading to non-leakage device exhibiting ∼100% capacitance retention after 3000 cycles. Graphical abstract: Cellulosic composites are developed as sustainable free-standing electrode and electrolyte for high performance electrochemical charge storage. Image, graphical abstract